2006
DOI: 10.1038/sj.ki.5001912
|View full text |Cite
|
Sign up to set email alerts
|

Peritoneal dialysis in the US: Evaluation of outcomes in contemporary cohorts

Abstract: Secular trends in dialysis therapy delivery require a frequent re-examination of outcomes in patients on renal replacement modalities. We examined four large cohorts of patients initiating peritoneal dialysis (PD) in 2000-2003 (total of >40 000 patients) to ascertain trends in patient outcomes, technique success, and predictors of both parameters of interest. Age, end-stage renal disease vintage, and diabetes were clear predictors of patient survival. Technique success was higher in patients on automated PD th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

21
192
6
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 186 publications
(220 citation statements)
references
References 46 publications
21
192
6
1
Order By: Relevance
“…Studies have found that as the cumulative numbers of PD patients treated increases, technique failure decreases significantly (2,77). In a recent study of over 40,000 PD patients, center size correlated inversely with the frequency of catheter problems (P Ͻ 0.0001), inadequate dialysis (P Ͻ 0.01), and infectious complications (P Ͻ 0.01) (2).…”
Section: Dialysis Center Sizementioning
confidence: 99%
See 2 more Smart Citations
“…Studies have found that as the cumulative numbers of PD patients treated increases, technique failure decreases significantly (2,77). In a recent study of over 40,000 PD patients, center size correlated inversely with the frequency of catheter problems (P Ͻ 0.0001), inadequate dialysis (P Ͻ 0.01), and infectious complications (P Ͻ 0.01) (2).…”
Section: Dialysis Center Sizementioning
confidence: 99%
“…Age, presence of diabetes, ESRD etiology, and ESRD vintage are all independent predictors of patient survival (2). For each 1-year increase in age, the risk of death increases by 4% [adjusted hazard ratio (HR) 1.04, P Ͻ 0.0001].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…It is suggested that a propensity to exploit technical and non-technical advances in PD increases directly with experience and that the centers become more adept at selecting patients to receive PD and treating their complications. 49 This is illustrated by the excellent PD catheter outcomes at our PD center, which is one of the largest PD centers in the United States, treating about 120 patients. 45 Most of the U.S. PD programs are small, however, typically comprising 10-15 PD patients.…”
Section: Growing a Pd Programmentioning
confidence: 99%
“…This number has many possible implications such as, but not limited to, inability to train a new patient in a timely manner; inability to do quality improvement; lack of nursing/center experience; and lack of a robust infrastructure to support patients and physicians as far as protocols and individualization of care. It has been shown that there is a strong association between center size and outcomes in PD patients (27,28). These and other subtle variables may influence how robustly home therapies are offered at an individual dialysis center.…”
Section: What Is Unique About the Us Renal Replacement Community?mentioning
confidence: 99%